Reconciliation Proceedings of the 25th International Conference of Jesuit Ecumenists Clongowes Wood, Ireland, July 8-13, 2019 - Rausch, Thomas P.; Schmidt, Markus (innsbruck university press, 2021)
The 25th International Ecumenists Congress of Jesuit Ecumenists met at Clongowes Wood in County Kildare, Ireland, from July 8-13, 2019, a return to the Emerald Isle after the 18th Congress met there in 2005. This last Congress drew some 15 Jesuits from around the world to focus on the topic of reconciliation. The formal papers are presented in these Proceedings. Much more difficult to capture is the personal interaction, the exchanges or brief reports to the full assembly, the marvelous hospitality of the Jesuit Community at Clongowes, let alone the conviviality enjoyed by our late evening gatherings or at the banquet graciously hosted in the castle by the Jesuit Community.